Vulnerability and the mind: symbolic conflicts between institutional diagnosis and the perspective of young people serving social-educational measures - Malvasi, Paulo Artur; Adorno, Rubens de Camargo Ferreira (Saúde e Sociedade, 2014)
Over the last two decades, the use of the term vulnerability has been expanded to several knowledge and intervention fields. This article examines the use of the idea of vulnerability in the socio-educational system as a component of power relations between institutions performing educational measures and adolescents. Based on ethnographic research conducted in the metropolitan area of São Paulo in 2009, 2010 and 2011, with the participation of fourteen teenagers serving social-educational measures, the paper analyzes the conflict between the psychological report of a young man and his own interpretation when talking about the same aspects of his life. The article discusses how the adolescent, who is differently intricated by distinct codes, experiences a reality shock which has escaped socio-educational system practices in their own existence. The meeting of the idea of vulnerability in the psychological report with the perspective of the mind as an attribute of a young man, creates a field of symbolic disputes between visions of the individual’s capacity for self-regulation.